PELAKSANAAN KEPEMIMPINAN CAMAT UNTUK MENINGKATKAN KINERJA PEGAWAI DI KECAMATAN SERASAN KABUPATEN NATUNA - Saputra E.21110114, Iwan (FISIP Universitas Tanjungpura, 2013)
To describe Serasan subdistrict leadership in improving the performance of employees in administrative services and matters relating to and affecting the performance of the employee . The results showed that the optimal sub-district Serasan not perform , his leadership role in applying the principles or proper leadership techniques to improve the performance of employees . It is characterized by weakness district head who does not have the ability to adapt to the demands and changes , in addition to the sub-district has not been able to increase the productivity of employees working and have not felt the presence of job satisfaction for employees . The factors that lead to decreased employee performance include: the employee has not professionals in the field of work . Incentive system is uneven and not well targeted , where the vision - mission does not function as it should . The organizational structure is not filled by the employee in accordance with the rank and expertise , and not the creation of harmonious cooperationamongemployeesÂ Key Word : Â Leadership District Head, Employee Performance.